EFFORTS TO PREVENT SECURITY AND ORDER DISTURBANCES BY THE BRIMOB CORP THROUGH PATROLS AND ON-SITE ACTION BASED ON THE DISCRETIONAL AUTHORITY OF THE POLICE - Hananto, Dwi; Nuraeny, Henny; Nurwati (DE'RECHTSSTAAT, 2024)
Many criminal cases occur in the Jabodetabek area with various types, including murder, rape, robbery, mugging, ganging up, theft, pickpocketing, to the lightest such as bullying. This study aims to determine and analyze efforts to prevent disturbances to security and order by the Brimob Corps through patrols and on-site action based on the discretionary authority of the Police. Empirical legal research is research that examines community behavior as a legal issue. In this study, the object of study is deviant behavior in the form of disturbances to security and order. To make patrol activities effective, namely: (1) Preparation of personnel, (2) Provision of facilities, (3) Knowing field conditions, (4) Patrolling at the right time, (5) Coordinating with village governments, mass organizations, and figures in each area to be patrolled. Discretion is the authority given to police officers to act based on their considerations in certain circumstances. The actions that can be taken are: (1) Preventing criminal acts which include: Soft hand-to-hand control, Hard hand-to-hand control, Control of blunt weapons, chemical weapons including tear gas, chili spray or other tools according to police standards, (2) Arresting the perpetrator, (3) Confiscating all evidence, (4) Taking action to stop activities which have the potential to cause disturbances to security and order.